The potential risks of chronic fluoride exposure on nephrotoxic via altering glucolipid metabolism and activating autophagy and apoptosis in ducks. (September 2021) - Li, Yangwei; Liu, Yingwei; Yi, Jiangnan; Li, Yuanliang; Yang, Bijing; Shang, Peng; Mehmood, Khalid; Bilal, Rana Muhammad; Zhang, Hui; Chang, Yung-Fu; Tang, Zhaoxin; Wang, Yajing; et al.
Graphical abstract: Fluoride exposure could damage the structure of kidney, induce the nephron-toxicity by activating autophagy, apoptosis and glucolipid metabolism pathways suggesting that fluorine exposure poses a risk of poisoning. This is the first study to reveal regulation mechanism of autophagy and apoptosis associated with glucolipid metabolism in NaF-induced nephron-toxicity, which provide important reference for environmental toxicology. Abstract: Fluoride is one of the most widely distributed elements in nature, while some fluorine-containing compounds are toxic to several vertebrates at certain levels. The current study was performed to evaluate the nephrotoxic effects of fluoride exposure in ducks. The results showed that the renal index was decreased in NaF group, and fluoride exposure significantly decreased the levels of serum Albumin, Glucose, Total cholesterol, Urea, protein and Triglycerides, confirming that NaF exhibited adverse effects on the kidney. The overall structure of renal cells showed damage with the signs of nuclelytic, vacuolar degeneration, atrophy, renal cystic cavity widening after fluoride induction. Renal vascular growth was impaired as the expression of VEGF and HIF-1α decreased (p > 0.05). More importantly, autophagy and apoptosis levels of CYT C, LC3, p62, Beclin, M-TOR, Bax and Caspase-3 were increased (p < 0.05) in the NaF treated group. Interestingly, our results showed that Phosphatidylethanolamine (PE) and Phosphatidylcholine (PC) activated the M-TOR autophagy pathway. Meanwhile, the PE acted on Atg5/ LC3 autophagy factor, followed by the auto-phagosome generation and activation of cell autophagy. These results indicate that NaF exposure to duck induced nephron-toxicity by activating autophagy, apoptosis and glucolipid metabolism pathways, which suggest that fluorine exposure poses a risk of poisoning.